Performative Mistakes and Practical Knowledge - (:unkn) unknown (My University, 2023)
A performative mistake is a mistake an agent makes when she fails to realize what she intends to bring about in the world. In this paper, I argue that performative mistakes create a puzzle for anyone who thinks that practical knowledge is required to act intentionally; it is not clear whether someone can continue an action she was doing after she commits a performative mistake. Against Adrian Haddock’s view of performative mistakes, I argue that such mistakes affect practical knowledge and therefore, cause an action process to cease. By emphasizing the deep relation between practical knowledge and practical reasoning, I show that an agent can continue an action after a performative mistake if she properly guides herself to the particular circumstances which make her previous practical reasoning applicable again.
Keywords: action; agency; Anscombe; mistake; practical knowledge